Analytical solution of the associative mean spherical approximation for the ion-dipole model - Holovko, M.F.; Kapko, V. (Condensed Matter Physics, 1998)
A simple electrolyte in a polar solvent is modelled by a mixture of polar hard spheres and equal diameter charged hard spheres with the possibility of ionic dimerization. The analytical solution of the associative mean spherical approximation (AMSA) for this model is derived to its full extent. Explicit expressions for pair correlation functions and dielectric constant in terms of the AMSA are established. Some numerical calculations illustrate the role of ionic association.